Learning Strategies at Muhammadiyah 1 Taman Sidoarjo During Pandemic Covid 19 - Harits Arba Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of this study was to analyze the effectiveness of implementing the learning from home (BDR) process during the Covid-19 pandemic at SMK Muhammadiyah 1 Taman. This study uses a qualitative method. The data collection technique used is a questionnaire given to students once a month. The subjects of this study were students of SMK Muhammadiyah 1 Taman. Based on the results of research conducted by filling out questionnaires, in general the implementation of home learning (BDR) for SMK Muhammadiyah 1 Taman students is quite effective with a percentage of 60-79%. The results of the questionnaire on the implementation of BDR learning that have poor effectiveness with 48% criteria are in the evaluation process. It is recommended that in learning from home (BDR), teachers are able to design learning activities from planning to evaluation in a simpler, more creative and effective way. Keywords: Covid-19, Access to Learning, Learning from Home.